Navigating futures: Theoretical perspectives on university students' employability perceptions and entrepreneurial aspirations - Mbuli, S; Isabirye, AK; Mathapelo, M (Edelweiss Applied Science and Technology, 2025)
This study explores the intricate bond between students' views on their employment readiness and their entrepreneurial goals. A qualitative literature review methodology was used to analyze current research, which provides a comprehensive understanding of student perceptions regarding their market readiness and entrepreneurial ambitions. The literature review methodology was chosen because it allows for the integration of extensive qualitative and quantitative data with theoretical findings from various studies. The conceptual framework established through this research enables a robust interpretation of how students perceive their employability and develop entrepreneurial intentions. The research data was retrieved from scholarly databases including JSTOR, Google Scholar, Scopus, and SpringerLink to include relevant high-quality research articles. This article pursues three primary objectives: i) a theoretical examination of university students' employability perceptions, ii) an analysis of factors influencing entrepreneurial intentions, and iii) an evaluation of how higher education affects employability and entrepreneurial mindset development. The study addresses the current knowledge gap regarding university students' understanding of their employability in relation to entrepreneurship during a period of technological change and economic instability in the job market. The research results offer an advanced understanding of how students' internal confidence levels and academic and environmental economic factors either support or challenge their ability to enter the workforce and pursue entrepreneurship. The research combines theoretical approaches to these constructs, providing essential knowledge for universities to develop curricula that enhance both employability and entrepreneurial skills. The study contributes to the ongoing discussion about university strategies to prepare students for future challenges in complex modern labor markets.